Effect of fertigation frequency on onion (Allium cepa) yield and soil nitrate-nitrogen - Patel, Neelam; Rajput, T.B.S (The Indian Journal of Agricultural Sciences, 2005)
A field experiment was conducted during 3-winter seasons of 2001-2002 through 2003-2004 to study the effect of fertigation daily, alternate day, weekly and monthly on an Indo-American hybrid 'Creole Red' of onion (Allium cepa L.) crop and NO3-N of soil. Analysis of soil samples indicated considerable influence of fertigation frequency on NO3-N distribution in soil profile. The NO3-N in lower soil profiles (30-60 cm soil depth) was marginally affected in daily, alternate day and weekly fertigation 41.9,42.0,43.6 ppm, respectively. However, fluctuations of NO3-N concentration in 0-15 cm, 15.0-30 cm, 30-45 cm and 45-60 cm soil depth was more in monthly fertigation frequency. After the crop season 29.85% NO3-N was leached through the profile in monthly fertigation. Daily, alternate day and weekly fertigation did not significantly affect yield of onion, 29.2 tonnes/ha, 28.0 tonnes/ha, 27.4 tonnes/ha respectively. The highest yield wasrecorded in daily fertigation (29.2 tonnes/ha) followed by alternate day fertigation (28 tonnes/ha) while the lowest in monthly fertigation (22.4 tonnes/ha). Application of 57.7 cm irrigation water and 3.4 kg/ha urea in daily fertigation resulted in maximum yield of onion (29.2 tonnes/ha) with least amount of leaching of NO3-N (23%).